Electronic Journal of Differential Equations, Vol. 2010 (2010), No. 23, Pp. 1-10. ISSN: 1072-6691. URL: Http://ejde - Math.txstate - Edu or Http://ejde - Math.unt - Edu FTP Ejde - Math.txstate - Edu
Electronic Journal of Differential Equations, Vol. 2010 (2010), No. 23, Pp. 1-10. ISSN: 1072-6691. URL: Http://ejde - Math.txstate - Edu or Http://ejde - Math.unt - Edu FTP Ejde - Math.txstate - Edu
Electronic Journal of Differential Equations, Vol. 2010 (2010), No. 23, Pp. 1-10. ISSN: 1072-6691. URL: Http://ejde - Math.txstate - Edu or Http://ejde - Math.unt - Edu FTP Ejde - Math.txstate - Edu
TUNCAY CANDAN
1. Introduction
In this article, we study the oscillatory behavior of solutions to to n-order mixed
neutral functional differential equations with distributed deviating arguments
Z d Z d
[x(t) ± ax(t ± h) ± bx(t ± g)](n) = p x(t − ξ)dξ + q x(t + ξ)dξ, (1.1)
c c
d2
(x(t) ± x[t − τ ] ± x[t + σ]) + qx[t − α] + px[t + β] = 0
dt2
are encountered in the study of vibrating masses attached to an elastic bar [8], and
were studied by Grace and Lalli [4]. Later Grace extended their results to n-order
equations with n odd in [5], and with n even in [6]. Moreover, Grace [7] remarked
that the results for the n-order equations
dn
(x(t) + cx[t − h] + Cx[t + H]) + qx[t − g] + Qx[t + G] = 0
dtn
In recent years, Candan [2], and Candan and Dahiya [3] obtained some results
for distributed delays, which motivate us to study (1.1). For books related to this
topic, we refer the reader to [1, 8, 10].
A function x is said to be a solution of (1.1) if x(t) ± ax(t ± h) ± bx(t ± g) is n
times continuous differentiable and x(t) satisfies (1.1) for t ≥ t0 .
A nontrivial solution of (1.1), for all large t, is called oscillatory if it has no
largest zero. Otherwise, a solution is called non-oscillatory.
The purpose of this paper is to provide sufficient conditions, only on the coeffi-
cients and on limits of the integrals, to guarantee that (1.1) is oscillatory.
2. Main Results
The following lemmas will be used in our proofs.
h
Lemma 2.1 ([11]). Suppose that a and h are positive constants and a1/n n e > 1.
Then
(i) the inequality
x(n) (t) − ax(t + h) ≥ 0
has no eventually positive solutions when n is odd;
(ii) the inequality
x(n) (t) + ax(t − h) ≤ 0
has no eventually positive solutions when n is odd.
Lemma 2.2 ([9]). Let x(t) be a function such that it and each of its derivative up to
order (n − 1) inclusive are absolutely continuous and of constant sign in an interval
(t0 , ∞). If x(n) (t) is of constant sign and not identically zero on any interval of
the form [t1 , ∞) for some t1 ≥ t0 , then there exist a tx ≥ t0 and an integer m,
0 ≤ m ≤ n with n + m even for x(n) (t) ≥ 0, or n + m odd for x(n) (t) ≤ 0, and such
that for every t ≥ tx ,
m>0 implies x(k) (t) > 0, k = 0, 1, . . . , m − 1
and
m≤n−1 implies (−1)m+k x(k) (t) > 0, k = m, m + 1, . . . , n − 1.
Theorem 2.3. Suppose that b > 0, either
p(d − c) 1/n g + c
e > 1, (2.1)
b n
or (p + q)(d − c) 1/n g − d
e > 1, g > d, (2.2)
b n
and q(d − c) 1/n c
e > 1. (2.3)
1+a n
EJDE-2010/23 OSCILLATION OF SOLUTIONS 3
Then
Z d Z d
(n)
[x(t) + ax(t − h) − bx(t + g)] =p x(t − ξ)dξ + q x(t + ξ)dξ, (2.4)
c c
is oscillatory.
Proof. Let x(t) be a non-oscillatory solution of (2.4). We may assume that x(t) is
eventually positive; that is, there exists a t0 ≥ 0 such that x(t) > 0 for t ≥ t0 . If
x(t) is an eventually negative solution, the proof follows the same arguments. Let
z(t) = x(t) + ax(t − h) − bx(t + g), t ≥ t0 + h.
From (2.4), we have
Z d Z d
z (n) (t) = p x(t − ξ)dξ + q x(t + ξ)dξ (2.5)
c c
for t ≥ t1 ≥ t0 + h, which implies that z (n) (t) > 0. Then z (i) (t), i = 0, 1, . . . , n are
of constant sign on [t1 , ∞). We have two possible cases to consider: z(t) < 0 for
t ≥ t1 , and z(t) > 0 for t ≥ t1 .
Case 1: z(t) < 0 for t ≥ t1 . Let v(t) = −z(t). Then from (2.5), we obtain
Z d Z d
(n)
v (t) + p x(t − ξ)dξ + q x(t + ξ)dξ = 0. (2.6)
c c
On the other hand, since
0 < v(t) = −z(t) = −x(t) − ax(t − h) + bx(t + g) ≤ bx(t + g) for t ≥ t1 ,
there is a t2 ≥ t1 such that
v(t − g)
x(t) ≥ for t ≥ t2 . (2.7)
b
In view of (2.7) it follows from (2.6) that
p d q d
Z Z
(n)
v (t) + v(t − g − ξ)dξ + v(t − g + ξ)dξ ≤ 0 for t ≥ t3 > t2 . (2.8)
b c b c
It is clear that from either (2.6) or (2.8), v (n) (t) < 0 for t ≥ t3 . Therefore, by
Lemma 2.2 v (n−1) (t) > 0 for t ≥ t3 . Now, we want to show that v 0 (t) < 0 for
t ≥ t3 . Suppose on the contrary v 0 (t) > 0 for t ≥ t3 , then there exists a constant
k > 0 and t4 ≥ t3 such that
v(t − g − ξ) ≥ k, v(t − g + ξ) ≥ k
for t ≥ t4 and ξ ∈ [c, d]. Thus,
k(p + q)(d − c)
v (n) (t) ≤ − for t ≥ t4
b
and
k(p + q)(d − c)(t − t4 )
v (n−1) (t) ≤ v (n−1) (t4 ) − → −∞ as t → ∞,
b
which is a contradiction. Thus, v 0 (t) < 0 and therefore (−1)i v (i) (t) > 0 for t ≥ t4
and i = 0, 1, . . . , n. Then from (2.8), we have
p(d − c)
v (n) (t) + v(t − (g + c)) ≤ 0, (2.9)
b
4 T. CANDAN EJDE-2010/23
and
(p + q)(d − c)
v (n) (t) + v(t − (g − d)) ≤ 0, t ≥ t4 . (2.10)
b
Thus, from Lemma 2.1 (ii) and condition (2.1), (2.9) has no eventually positive
solutions or from Lemma 2.1 (ii) and condition (2.2), (2.10) has no eventually
positive solutions, which is a contradiction.
Case 2: z(t) > 0 for t ≥ t1 . Let
w(t) = z(t) + az(t − h) − bz(t + g), t ≥ t1 + h.
Thus, one can show that
Z d Z d
w(n) (t) = p z(t − ξ)dξ + q z(t + ξ)dξ, (2.11)
c c
then
Z d Z d
[w(t) + aw(t − h) − bw(t + g)](n) = p w(t − ξ)dξ + q w(t + ξ)dξ. (2.12)
c c
Since n is odd, by Lemma 2.2 z 0 (t) > 0 for t ≥ t∗2 ≥ t1 + h. From equation
(2.11), w(n) (t) > 0 and w(n+1) (t) > 0 for t ≥ t∗3 ≥ t∗2 . Therefore, w(i) (t) > 0 for
i = 0, 1 . . . , n + 1 and t ≥ t∗3 . Using this results and (2.12) we obtain
Z d Z d Z d
(n)
(1 + a)w (t) ≥ p w(t − ξ)dξ + q w(t + ξ)dξ ≥ q w(t + ξ)dξ
c c c
and then
q(d − c)
w(n) (t) ≥ w(t + c), t ≥ t∗3 .
1+a
This last equation does not have a positive solution by Lemma 2.1 (i) and condition
(2.3). Therefore, it is a contradiction, and the proof is complete.
so that n = 3, a = b = 1, c = π2 , d = 3π, p = q = 21 , h = π, g = 9π
2 . One can verify
that the conditions of Theorem 2.3 are satisfied. We shall note that x(t) = cos t is
a solution of this problem.
Theorem 2.5. Suppose c > h, c > g, a > 0,
p(d − c) 1/n c − h
e > 1, (2.13)
a n
q(d − c) 1/n c − g
e > 1. (2.14)
1+b n
Then
Z d Z d
(n)
[x(t) − ax(t − h) + bx(t + g)] =p x(t − ξ)dξ + q x(t + ξ)dξ, (2.15)
c c
is oscillatory.
EJDE-2010/23 OSCILLATION OF SOLUTIONS 5
As in the proof of the Theorem 2.3 (case 2), we have w(i) (t) > 0 for t ≥ t∗2 ≥ t1
and i = 0, 1, . . . , n + 1. Then, we obtain
Z d Z d Z d
(1 + b)w(n) (t + g) ≥ p w(t − ξ)dξ + q w(t + ξ)dξ ≥ q w(t + ξ)dξ.
c c c
0
Since w (t) > 0 for t ≥ t∗2 ,
q(d − c)
w(n) (t) ≥ w(t + (c − g)).
1+b
The above equation does not have a positive solution by Lemma 2.1 (i) and condi-
tion (2.14). Thus, the proof is complete.
6 T. CANDAN EJDE-2010/23
and then
Z d Z d
[w(t) + aw(t − h) + bw(t + g)](n) = p w(t − ξ)dξ + q w(t + ξ)dξ. (2.23)
c c
Since z(t) > 0 and z 0 (t) > 0 are eventually increasing, from (2.22) we see that
w(n) (t) > 0 and w(n+1) (t) > 0 for t ≥ t2 ≥ t1 . As a result of this w(i) (t) > 0 for
i = 0, 1, . . . , n + 1 and t ≥ t2 . Thus from (2.23), we have
Z d
(1 + a + b)w(n) (t + g) ≥ q w(t + ξ)dξ,
c
so that n = 3, a = b = 1, c = 5π 7π 1 3π
2 , d = 2 , p = q = 4 , h = π, g = 2 . One can see
that the conditions of Theorem 2.10 are satisfied. In fact x(t) = sin t + cos t is an
oscillatory solution of this problem.
The proofs of the following two theorems are similar to that of Theorem 2.10
and therefore omitted.
Theorem 2.12. Suppose that c > g > h, and (2.20) holds. Then the equation
Z d Z d
[x(t) + ax(t + h) + bx(t + g)](n) = p x(t − ξ)dξ + q x(t + ξ)dξ,
c c
is oscillatory.
8 T. CANDAN EJDE-2010/23
Then
Z d Z d
w(n) (t) + p v(t − ξ)dξ + q v(t + ξ)dξ = 0 (2.31)
c c
and since the function satisfies (2.27), we obtain
Z d Z d
[−w(t) + aw(t − h) + bw(t + g)](n) + p w(t − ξ)dξ + q w(t + ξ)dξ = 0.
c c
If w(t) < 0 for t ≥ t1 , we can handle as in case 1. Now suppose w(t) > 0 for t ≥ t1 .
On the other hand, v 0 (t) < 0 for t ≥ t2 ≥ t1 , otherwise from (2.31) we see that
w(n) (t) < 0 and w(n+1) (t) < 0 for t ≥ t2 which is a contradiction. As a result of
this,
(−1)i w(i) (t) > 0 for i = 0, 1, . . . , n + 1 and t ≥ t2 ,
and then
Z d
(n)
(a + b)w (t − h) + p w(t − ξ)dξ ≤ 0,
c
p(d − c)
w(n) (t) + w(t − (c − h)) ≤ 0,
a+b
which leads to a contradiction by condition (2.25) and Lemma 2.1 (ii). This com-
pletes the proof.
g = 2π. Clearly the conditions of Theorem 2.14 are satisfied. In fact, x(t) = sin t
is a solution of this problem.
The proofs of the following two theorems are similar to that of Theorem 2.14,
hence the proofs are omitted.
Theorem 2.16. Suppose a > 0, h > g, and (2.25) and (2.26) hold. Then
Z d Z d
[x(t) − ax(t − h) − bx(t − g)](n) = p x(t − ξ)dξ + q x(t + ξ)dξ,
c c
is oscillatory.
Theorem 2.17. Suppose b > 0, h > g, λ = µ = −1, α = β = 1. In addition, if
(2.26) and
p(d − c) 1/n c + g
e > 1,
a+b n
Then
Z d Z d
[x(t) − ax(t + h) − bx(t + g)](n) = p x(t − ξ)dξ + q x(t + ξ)dξ,
c c
is oscillatory.
10 T. CANDAN EJDE-2010/23
References
[1] D. D. Bainov and D. P. Mishev; Oscillation Theory for Neutral Differential Equations with
Delay, Adam Hilger, Bristol, 1991.
[2] T. Candan; Oscillation behavior of solutions for even order neutral functional differential
equations, Appl. Math. Mech. Engl., 27 (10) (2006), 1311-1320.
[3] T. Candan and R. S. Dahiya; On the oscillation of certain mixed neutral equations, Appl.
Math. Lett., 21 (3) (2008), 222-226.
[4] S. R Grace and B. S. Lalli; Oscillation theorems for second order neutral functional differential
equations, Appl. Math. Comput., 51 (1992), 119-133.
[5] S. R Grace; Oscillation criteria for nth-order neutral functional differential equations, J.
Math. Anal. Appl., 184 (1994), 44-55.
[6] S. R Grace; On the oscillations of mixed neutral equations, J. Math. Anal. Appl., 194 (1995),
377-388.
[7] S. R Grace; Oscillation of mixed neutral functional differential equations, Appl. Math. Com-
put., 68 (1) (1995), 1-13.
[8] J. Hale; Theory of Functional Differential Equations, S pringer-Verlag, New York, 1977.
[9] I. T. Kiguradze; On the oscillation of solutions of the equation dm u/dtm +a(t)|u|m signu = 0,
M at. Sb., 65 (1964), 172-187.
[10] G. S. Ladde, V. Lakshmikantham and B. G. Zhang; Oscillation Theory of Differential Equa-
tions with Deviating Arguments, M arcel Dekker, Inc., New York, 1987.
[11] G. Ladas and I. P. Stavroulakis; On delay differential inequalities of higher order, C annad.
Math. Bull., 25 (1982), 348-354.
Tuncay Candan
Department of Mathematics, Faculty of Art and Science, Niğde University, Niğde,
51200, Turkey
E-mail address: [email protected]